PENGARUH OPINI AUDIT DAN REPUTASI AUDITOR TERHADAPAUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAIVARIABEL MODERASI: UKURAN PERUSAHAAN - Thomas Harta Zebua (Yayasan Kayyis Mulia Jaya, 2026)
This study aims to empirically demonstrate the influence of audit opinion and auditor reputation on audit delay, moderated by company size. This study uses associative quantitative research and uses secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The population in this study was 83 companies in the food and beverage sub-sector for the 2020-2024 period. The sampling technique was purposive sampling, resulting in 54 companies or 270 observations. Hypothesis testing uses panel data regression analysis and Moderated Regression Analysis (MRA). The F test results indicate that audit opinion and auditor reputation simultaneously influence audit delay. The t-statistical test results indicate that audit opinion and auditor reputation partially influence audit delay. While the Moderated Regression Analysis (MRA) test shows that company size is able to moderate the influence of audit opinion on audit delay with a strengthening nature, while company size is able to moderate the influence of auditor reputation on audit delay with a weakening nature. Keywords: Audit Opinion, Auditor Reputation, Audit Delay, Company Size.